Farmer field schools as a methodology for diagnosis, modelling and decision support for animal health and production interventions - Buyu, G.; Minjauw, B. (European Union, 2003)
In government of Kenya provided veterinary services to livestock keepers including clinical and extension services, the state started to gradually withdraw its services. So the need for alternative methods for disseminating technologies is recognised. In the interest of ensuring that farmers are sufficiently involved in research and Development, a growing number of organisations are seeking alternative models generally classify as 'farmer-led' extension methods. The Farmer Field School (FFS) approach was originally developed by FAO to introduce the benefits of integrated pest management practices to rice farmers in Asia through 'learning by doing'. The International Livestock Research Institute (ILRI) Livestock Farmer Field School Project (LFFS), started in April 2001 and funded by the DFID Animal Health Programme and FAO, is adopting and testing the FFS methodology for animal health and Production, focusing upon small-holder dairy farmers. The paper illustrates the links between farmers' practice and knowledge models that a FFS process uses. Also LFFS approach is discussed.